Pancreas transplantation perceptions and practice: Results from a national US survey. Issue 10 (6th August 2021) - Parsons, Ronald F.; Matar, Abraham; Lentine, Krista L.; Woodside, Kenneth J.; Singh, Neeraj; Alhamad, Tarek; Basu, Arpita; Cabeza Rivera, Franco H.; Cheungpasitporn, Wisit; Romeo, Giulio; Rao, Swati; Kensinger, Clark D.; et al.
Abstract: Background: Due to a substantial decline in pancreas transplantation (PT) across the United States over the past 15 years, we sought to understand the perceptions and practices of US PT programs. Methods: Surveys were sent to members of the American Society of Transplantation Surgeons and the American Society of Transplantation by email and professional society postings between August 2019 and November 2019. Results: One hundred twenty three responses were recorded from 56 unique programs. Program characteristics were obtained from the Scientific Registry of Transplant Recipients. Respondents were transplant surgeons (71%), transplant nephrologists (17%), trainees (9%), and allied professionals (3%). Programs were defined according to annual volume as: low (<5 PT/year), intermediate (6–20), or high (>20). High‐volume programs reported that these factors were most important for increased PT: expansion of recipient selection, more aggressive donor utilization, and hiring of PT program‐specific personnel. At both the program and national level, the vast majority (82% and 79%, respectively) felt the number of PTs currently performed are not in balance with patients' needs. Conclusions: Overall, programs reported that the option of PT is not offered adequately to diabetic patients and that strategies to maintain higher PT volume are most evident at intermediate, and especially, high‐volume programs.